STATE AND PROSPECTS FOR DEVELOPMENT OF RAPID PROTOTYPING TECHNOLOGIES IN INDUSTRY (Part Оne) - L. A. Kolesnikov; G. P. Mangula; V. K. Sheleh; A. M. Iakimovich (Наука и техника)
Growth dynamics pertaining to country- and industry branch-wise application of additive technologies is presented in the paper. The paper contains application examples of these technologies with a view of rapid manufacturing. Specific concrete recommendations are proposed for quicker introduction of additive manufacturing technologies in domestic industry.